REKAYASA PENGURAIAN KEPADATAN LALU LINTAS PADA SIMPANG TIGA TAK BERSINYAL (STUDI KASUS: JALAN PERMANDIAN ALAM DAN JALAN H.DAENG BETA MAKASSAR ) - Dwychy Irwanto; Hendry Tanoto Kalangi; Mursalim (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2023)
Traffic congestion is a situation where traffic flow is hampered or stopped due to obstruction of vehicle mobility. The problem of traffic jams seems to have become a special characteristic of Makassar City. Times that are prone to traffic jams are when going to school, going to work, coming home from work, weekends and holidays plus the population growth of vehicles is not proportional to the capacity of roads in Makassar City. This study models 2 alternative engineering plans by changing the geometric conditions of the road at the unsignalized intersection of Jalan Permandian Alam and Jalan H. Daeng Beta Makassar. The software used is PTV Vissim 2023 and Measure Distance to measure the queue length that occurs. The results of the research from the 2 alternative engineering plans and the existing conditions show that the existing condition in the afternoon has the highest queue length, Permandian Alam Road (North) with a length of 526m, Permandian Alam Road (south) with a length of 194m and Jalan H. Daeng Beta with a length of 105m. After conducting experiments on 2 engineering alternative plans, it was concluded that alternative 2 was the most optimal twin bridge design engineering with a queue length at the intersection of Jalan Bathing (North) of 236m, Jalan Bathing Alam (South) of 143m, and Jalan H.Daeng Beta of 65m.